Economic Resource Analysis of Water in The Long-Term Economic Development Plan Badung District 2025—2045 - I Nyoman Tingkes; Ida Ayu Putu Sri Widnyani; I Made Sumartana (Green Publisher Indonesia, 2025)
The purpose of this study is to determine the carrying capacity of land for residential areas in the Regional Long-Term Development Planning of Badung Regency 2025–2045. This research is a documentary research using quantitative data sourced from the 2023 Badung Regency Strategic Environmental Assessment Document. The quantitative data was analyzed using the runoff coefficient analysis technique to calculate water availability. In addition, conversion techniques are also used to calculate the needs of residents for water to live a decent life. The results of documentary research can find that for 2025-2045 Badung Regency has a water surplus status of 97,378.00 m3. However, if you look at the needs of the population per village/per sub-district for water, it can be seen that there are as many as fifteen villages with a water deficit. In addition, it can also be known that the construction of hotels, housing, and other physical developments that are carried out massively, which is accompanied by the use of groundwater as much as 4,846 m3/month, can cause land subsidence and encourage flash floods.